PRODUKSI GULA AREN CETAK MILIK ANGGOTA KTH HARAPAN BARU I DI KELURAHAN BATU PUTUK, KOTA BANDAR LAMPUNG - Putri, Pascalina Yossy; Indriyanto, Indriyanto; Asmarahman, Ceng (MAKILA, 2022)
The availability of palm sap will determine the production of palm sugar. Therefore, the research objective is to know the palm sugar production in the sugar industry of the Harapan Baru I Forest Farmers Group at Batu Putuk Village. The research data was gathered through observing and interviewing palm sugar industry owners. According to the research, the average volume of processed sap per day was 46.125 liters (50.737 kg/day) from 16 palm trees. The average palm sugar yield is 12.57 percent, and the average palm sugar production is 6.53 kg/day. The right strategy to develop molded palm sugar production was to maintain palm plants and improve tapping techniques to increase the volume of palm sap and palm sugar production.